Analisis Presuposisi Dalam Wacana Iklan "Raya Takaful Ikhlas 2024” - Citra Riskya Simanjuntak; Intan Sri Devi Sitorus; Najwa Sabrina Putri; Ratih Susanti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Advertising as one of the forms of communication has an important role in introducing a product that is goods or services to the society. And advertising is one of the parts of the discourse, which is called the advertising discourses. This study aims to describe the assumption analysis in the Takaful Ikhlas 2024 publicity discourse. As for the method used in this research, it is qualitative descriptive. The source of the data used is data collected using the technique of logging and logging. The researchers took a video of the Takaful Ikhlas 2024 publicity, and then recorded all the announcements for classification and analysis. The subject of this study is Takaful Ikhlas 2024. Data analysis process using data reduction, data display (data presentation), conclusion withdrawal (verification). The results of the study found that there are six types of assumptions found: 1) factual assumption (following the vocabulary that can be considered as a fact), 2) non-factual (assuming not true), 3) structural (constantly and conventionally that the part of the structure has been assumed to be true), 4) lexical (interpreting not expressed as understood), 5) existential (associating the existence of an existence), and 6) contractual (not just untrue but the opposite of the truth or not of the fact).